Characterization of Novel P-Selectin Targeted Complement Inhibitors in Murine Models of Hindlimb Injury and Transplantation - Zheng, Chaowen; Ricci, Jerec; Zhang, Qinqin; Alawieh, Ali; Yang, Xiaofeng; Nadig, Satish; He, Songqing; Engel, Pablo; Jin, Junfei; Atkinson, Carl; Tomlinson, Stephen (Frontiers in Immunology, 2021)
The complement pathway has long been recognized as a potential druggable target for a variety of inflammatory conditions. Very few complement inhibitors have been approved for clinical use, but a great number are in clinical development, nearly all of which systemically inhibit complement. There are benefits of targeting complement inhibition to sites of activation/disease in terms of efficacy and safety, and here we describe P-selectin targeted complement inhibitors, with and without a dual function of directly blocking P-selectin-mediated cell-adhesion. The constructs are characterized in vitro and in murine models of hindlimb ischemia/reperfusion injury and hindlimb transplantation. Both constructs specifically targeted to reperfused hindlimb and provided protection in the hindlimb ischemia/reperfusion injury model. The P-selectin blocking construct was the more efficacious, which correlated with less myeloid cell infiltration, but with similarly reduced levels of complement deposition. The blocking construct also improved tissue perfusion and, unlike the nonblocking construct, inhibited coagulation, raising the possibility of differential application of each construct, such as in thrombotic vs. hemorrhagic conditions. Similar outcomes were obtained with the blocking construct following vascularized composite graft transplantation, and treatment also significantly increased graft survival. This is outcome may be particularly pertinent in the context of vascularized composite allograft transplantation, since reduced ischemia reperfusion injury is linked to a less rigorous alloimmune response that may translate to the requirement of a less aggressive immunosuppressive regime for this normally nonlife-threatening procedure. In summary, we describe a new generation of targeted complement inhibitor with multi-functionality that includes targeting to vascular injury, P-selectin blockade, complement inhibition and anti-thrombotic activity. The constructs described also bound to both mouse and human P-selectin which may facilitate potential translation.